Suppressing mechanical property variability in recycled plastics via bioinspired design - Dimitrios Georgiou; Danqi Sun; Xing Liu; Christos E. Athanasiou (Proceedings of the National Academy of Sciences, 2025)
Over 350 million metric tons of plastic waste are generated annually, with most ending up in landfills, dumps, or the environment, posing significant risks. Mechanical recycling remains underutilized, largely due to the high variability in the mechanical properties of recycled plastics (recyclates). This variability undermines performance reliability and hinders the adoption of recyclates in demanding industrial applications. Inspired by natural materials, known for their mechanical robustness despite microstructural stochasticity, we propose a universal, chemistry-agnostic, brick-and-mortar design tailored for recycled polymers. In this design, stiff recycled plastic platelets (bricks) are embedded in a soft virgin polymer matrix (mortar), which accommodates deformation and redistributes stress. To predict the effective modulus, strength, and property variability of such structures, we developed an uncertainty-aware tension-shear-chain model, combining Monte Carlo simulations with literature-based distributions of recyclates’ stiffness and conservative interfacial parameter stochasticity assumptions. We validated our model using nacre-inspired composites fabricated from recycled high-density polyethylene (rHDPE) platelets and polydimethylsiloxane (PDMS) mortar. The experimental results matched model predictions, confirming significant suppression of variability. In a case study on industrial HDPE stretch film, our design reduced modulus variability by up to 93% and maximum permissible strain variability by at least 68% compared to input rHDPE, while matching the modulus of virgin HDPE film. This work introduces a design-enabled variability-suppression strategy for recycled plastics, able to transform highly heterogenous materials into structurally robust products. By supporting virgin-plastic substitution and circular design strategies, our approach can enable the broader adoption of recyclates by several industries.